Online System for Power Quality Operational Data Management in Frequency Monitoring Using Python and Grafana - Jose-María Sierra-Fernández; Olivia Florencias-Oliveros; Manuel-Jesús Espinosa-Gavira; Juan-José González-de-la-Rosa; Agustín Agüera-Pérez; José-Carlos Palomares-Salas (Energies, 2021)
This article proposes a measurement solution designed to monitor the instantaneous frequency in power systems. It uses a data acquisition module and a GPS receiver for time stamping and traceability. A Python-based module receives data, computes the frequency, and finally transfers the measurement results to a database. The frequency is calculated with two different methods, which are compared in the article. The stored data is visualized using the Grafana platform, thus demonstrating its potential for comparing scientific data. The system as a whole constitutes an efficient, low-cost solution as a data acquisition system.